Selectivity and Specificity of Sphingosine 1-Phosphate Receptor Ligands: “Off-Targets” or Complex Pharmacology? - Pyne, Nigel J.; Pyne, Susan (Frontiers in Pharmacology, 2011)
A recent perspective published in frontiers of Pharmacology by Salomone and Waeber (2011) discussed the selectivity and specificity of sphingosine 1-phosphate (S1P) receptor ligands. This perspective surveyed the use of various S1P receptor ligands and attempted to reconcile a number of inconsistencies in the predicted biological outcomes: these were interpreted as ‘off-target’ effects. Therefore the perspective cautioned against the use of these S1P receptor ligands. Here we highlight the complex pharmacology of S1P receptors, which along with ‘inside-out’ signalling might provide an alternative explanation for ‘off-target’ effects.